PKC-Mediated ZYG1 Phosphorylation Induces Fusion of Myoblasts as well as of Dictyostelium Cells. (6th February 2012) - Amagai, Aiko; MacWilliams, Harry; Isono, Takahiro; Omatsu-Kanbe, Mariko; Urano, Shinya; Yamamoto, Kazuo; Maeda, Yasuo
Abstract : We have previously demonstrated that a novel protein ZYG1 induces sexual cell fusion (zygote formation) of Dictyostelium cells. In the process of cell fusion, involvements of signal transduction pathways via Ca 2+ and PKC (protein kinase C) have been suggested because zygote formation is greatly enhanced by PKC activators. In fact, there are several deduced sites phosphorylated by PKC in ZYG1 protein. Thereupon, we designed the present work to examine whether or not ZYG1 is actually phosphorylated by PKC and localized at the regions of cell-cell contacts where cell fusion occurs. These were ascertained, suggesting that ZYG1 might be the target protein for PKC. A humanized version of zyg1 cDNA ( mzyg1 ) was introduced into myoblasts to know if ZYG1 is also effective in cell fusion of myoblasts. Quite interestingly, enforced expression of ZYG1 in myoblasts was found to induce markedly their cell fusion, thus strongly suggesting the existence of a common signaling pathway for cell fusion beyond the difference of species.